Collaborative Governance Study of Collaborative Governance in Community-Based Housing Development in Kendal, Central Java - Martin Rambe; Eko Prasojo (Budapest International Research and Critics University, 2021)
A total of 7.6 million Indonesians do not own a house (BPS, 2019). Housing is a citizen's right (UUD 1945) and the central government is responsible for its fulfillment (Law No. 1/2011). The Directorate General of Housing of the Ministry of Public Works and Public Housing (PUPR) initiated the Community-Based Housing Development (P2BK) program in order to accelerate the construction of livable houses. The program that is already running is P2BK for the Curugsewu Asri Community in Kendal Regency, Central Java. This development is carried out with the ABCG (Academics, Business, Community, Government) collaboration model. The implementation of this collaboration faces various problems: there are community members who do not have regular income, there are different perceptions about the concepts used in the collaboration, there are different conditions among actors, and others. Researchers use collaborative governance theory from Emerson, Nabatchi, and Balogh (2012) as a guide for researchers to collect research data and analyze findings. This research uses qualitative methods by collecting data through in-depth interviews and literature studies. The results showed that the collaboration went quite well. Each actor has resources that are empowered to achieve goals and collaboration is within a policy and administrative framework and also there’s mutual trust. The most prominent factors that influence the success of collaboration are active leadership and consistent mentoring.